Investigation of the process of extraction of a highly starchy fraction of rye flour by air classification - N. R. Andreev; V. G. Goldstein; V. A. Kovalenok; L. P. Nosovskaya; L. V. Adikaeva; A. A. Miroshnikov (Аграрная наука Евро-Северо-Востока)
The article provides an overview of the current state of the application of solid-phase methods for separating the structure of grain and leguminous raw material into constituent components, as one of the most relevant areas of environmental protection and reducing the amount of wastewater from enterprises processing agricultural raw materials. The main direction of research on the production of protein concentrates from leguminous raw materials (peas, beans, chickpeas, lupine) by the method of air classification is noted. Among grain crops, rye stands out as having a more balanced amino acid composition compared to wheat and the largest starch grains up to 60 microns, which improves the aero-dynamic separation of grain flour into protein and starch fractions. Тherefore, rye flour was the object of research in this work. The research area included the development of a method for determining the starch content in the heavy fraction of rye flour from the yield of its light protein fraction and its starch content using an installation with variable parameters of a two-chamber disperser and a vortex classifier. The results of experiments on the separation of the mass of the initial rye flour into heavy starch and light protein fractions with a given ratio of starch and protein are theoretically justified and experimentally confirmed. The dependences of the starch content in the heavy fraction on the number of cycles of its recycling are established. With variable parameters of grinding rye flour, determined by the speed of the working bodies of the dispersant from 70 to 100 m/s, the time of grinding and recirculation of the heavy fraction of 30 s and the tangential speed of the classifier rotor of 15 m/s, stable results were obtained for the separation of starch and protein. Тhe yield of the heavy fraction of 72 % with a starch content of 85 % and the yield of the light fraction of 28 % with a mass fraction of protein of at least 26 %.